A PCB carbon film actuator for automobile air conditioning
By using homemade dispersants and nano-silicon dioxide in the carbon film actuator of automotive air conditioner dampers, the shortcomings of the carbon film feedback control method in terms of wear resistance, resistance uniformity and adhesiveness are solved, and a higher service life and control accuracy are achieved.
Patent Information
- Application Number
- CN202411542375.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The carbon film feedback control method of existing automotive air conditioning dampers has shortcomings in wear resistance, resistance uniformity and adhesiveness, which affects the service life and control accuracy of the actuator.
The homemade dispersant is used to disperse carbon black evenly, improve the interaction between carbon black and resin, thereby enhancing the adhesion performance of the carbon film and substrate, and nano-silica is added to improve wear resistance.
It improves the service life of the PCB carbon film actuator and the control accuracy of the air conditioner, significantly improving the wear resistance and resistance uniformity of the carbon film.
Smart Images

Figure CN119403031B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electronic components, and in particular relates to a PCB carbon film actuator for an automobile air conditioner. Background Art
[0002] With the continuous improvement of science and technology and living standards, people have put forward higher and higher requirements for the comfort of cars. Air conditioning actuators are widely used in automotive air conditioning actuators as devices that control the opening angle and torque output of air flow distribution dampers.
[0003] The carbon film feedback control method is currently the most common control method for the operation of automotive air-conditioning dampers. Its principle is: the angle sensor completes the closed control logic, and there are 5 external signal lines, namely: the positive pole of the power supply, the negative pole of the power supply, GND, 5V, and the signal line. The positive and negative poles of the power supply control the motor to rotate forward and reverse. GND and 5V are connected to the circuit so that the collected signal is within 0~5V respectively. The voltage value in the signal circuit is controlled through the external signal line so that the circuit stops at the required signal voltage position. Different feedback voltages are received through the control signal. When the input signal gives the required voltage, the gear shaft is connected to the motor to operate, and the output gear is controlled to stop when it reaches the given voltage, thereby ensuring that the given input voltage is the required position for the output, thereby accurately positioning the air-conditioning damper. The potentiometer carbon film feedback control method is similar to the ordinary carbon film feedback method, except that the brush and the circuit board are integrated into an integral embedded output gear rotating shaft. As an important component of the PCB carbon film actuator controller, the performance of the carbon film directly determines the service life of the actuator and the control accuracy of the air conditioner. In particular, the wear resistance of the carbon film, the uniformity of resistance, and the adhesion between the carbon film and the PCB substrate are very important. Summary of the invention
[0004] Based on this, the present invention provides a PCB carbon film actuator for automobile air conditioner, which uses a carbon film with high wear resistance and uniform film resistance change for the PCB carbon film actuator, thereby improving the service life of the actuator and the control accuracy of the air conditioner. Among them, the use of a homemade dispersant to evenly disperse carbon black can improve the interaction between carbon black and resin, thereby improving the bonding performance with the substrate, and adding nano-silicon dioxide to improve its wear resistance.
[0005] The technical solution for achieving the purpose of the present invention is as follows:
[0006] The present invention provides a PCB carbon film actuator for automobile air conditioner, wherein the PCB carbon film actuator is composed of a housing, a PCB circuit board, a first rotating gear, a second rotating gear, a third rotating gear, an output gear and a driving assembly; the PCB circuit board comprises a main PCB circuit board and a circular PCB circuit board; the main PCB circuit board comprises a substrate, a first spring brush, a wire and an arc carbon film; the circular PCB circuit board comprises a circular substrate, a second spring brush and a copper foil; one end of the first spring brush is fixed on the main PCB circuit board, and the other end is in contact with the copper foil, and is used for The circular PCB circuit board is connected with the circular PCB circuit board; the second elastic brush is fixed on the edge of the circular PCB circuit, one end of which is in contact with the circular arc carbon film, and slides on the circular arc carbon film through the rotation of the output gear; the circular arc carbon film is obtained by printing carbon film ink on the substrate and curing; the carbon film ink comprises the following components by weight: 20 to 35 parts of carbon material, 30 to 35 parts of resin, 1.5 to 2.5 parts of dispersant, 5 to 10 parts of solvent, and 1 to 1.5 parts of wear-resistant additive; the dispersant has the following molecular structure of Formula I:
[0007]
[0008] R in the molecular structure of Formula I has one or more of the following molecular structures:
[0009] --OH, --Cl and
[0010] It should be noted that the document Carbon Lett. 33, 531-548 (2023) successfully synthesized graphene by combining liquid phase exfoliation and hydrothermal method with various conductive surfactants perylene-3,4,9,10-tetracarboxylates, and proved that it is an ideal conductive surfactant for exfoliating graphene sheets, but perylene-3,4,9,10-tetracarboxylates have poor solubility in organic solvents; based on this, the present invention adopts perylene diimide derivatives as dispersants, which have good dispersibility in water and polar solvents, disperse graphite and carbon black, and maintain good conductive properties.
[0011] Preferably, the carbon material is at least one of carbon black and flake graphite.
[0012] More preferably, the carbon black has a particle size of 10 to 100 nm and an amorphous structure.
[0013] More preferably, the flake graphite has a particle size of 500 to 5000 nm and a flaky crystal structure.
[0014] Preferably, the substrate is one or more of a paper substrate, a glass cloth substrate and a composite substrate.
[0015] More preferably, the substrate is a glass cloth substrate.
[0016] Preferably, the driving assembly includes a motor and a worm; the first rotating gear is composed of a helical gear and a spur gear; the second rotating gear, the third rotating gear and the output gear are composed of spur gears; the worm of the driving assembly rotates to drive the first rotating gear, the first rotating gear is toothed with the second rotating gear, the second rotating gear is toothed with the third rotating gear, and the third rotating gear is toothed with the output gear.
[0017] Preferably, the resin is composed of epoxy resin, curing agent and diluent, and the mass ratio thereof is epoxy resin:curing agent:diluent=1:1:1.5.
[0018] Preferably, the epoxy resin is bisphenol A epoxy resin; the curing agent is at least one of methylhexahydrophthalic anhydride and hexahydrophthalic anhydride; and the diluent is at least one of 3,4-epoxycyclohexylcarboxylic acid-3,4-epoxycyclohexylmethyl ester and glycidyl alkyl ether.
[0019] Preferably, the solvent is at least one of ethylene glycol butyl ether and propylene glycol methyl ether acetate; and the wear-resistant additive is nano-silicon dioxide.
[0020] More preferably, the curing agent is methyl hexahydrophthalic anhydride; the diluent is 3,4-epoxycyclohexylcarboxylic acid-3,4-epoxycyclohexyl methyl ester; and the solvent is propylene glycol methyl ether acetate.
[0021] Preferably, R in the molecular structure of Formula I has the following molecular structure:
[0022]
[0023] Preferably, the dispersant is obtained by reacting perylene-3,4,9,10-tetracarboxylic anhydride with a dendrimer compound.
[0024] Specifically, the preparation method of the dendrimer compound is as follows:
[0025] 1) Under a nitrogen atmosphere, at a temperature of 0 to 5° C., tert-butyl N-(2,3-dihydroxypropyl)carbamate, tetrabutylammonium bromide (TBAB) and dichloromethane solvent are added to a three-necked flask, and then 3-bromopropylene and a sodium hydroxide aqueous solution are added. After the temperature is raised to 25 to 30° C., the mixture is stirred for 12 to 24 hours, and then diluted with water. The mixture is extracted three times with dichloromethane, dried over anhydrous magnesium sulfate, the solvent is removed by rotary evaporation, and the product 1 is purified by column chromatography;
[0026] 2) Under a nitrogen atmosphere, at a temperature of 0 to 5° C., slowly drop hydrogen peroxide into acetic acid, and stir for 1 to 2 hours to obtain a peroxide compound; dissolve the product 1 obtained in step 1) in dichloromethane, slowly drop the obtained peroxide compound at a temperature of 0 to 5° C., raise the temperature to 25 to 30° C., stir for 8 to 12 hours, add an excess of saturated sodium bicarbonate solution, continue stirring for 6 to 8 hours, extract with dichloromethane three times, dry over anhydrous magnesium sulfate, remove the solvent by rotary evaporation, and purify by column chromatography to obtain product 2;
[0027] 3) Repeat step 1), step 2), and step 1) for three steps in sequence, dissolve the product in a mixed solution of dichloromethane and trifluoroacetic acid at a temperature of 0 to 5° C., heat to 35° C., stir for 1 to 2 hours, add an excess of saturated sodium bicarbonate solution, extract with dichloromethane three times, dry over anhydrous magnesium sulfate, remove the solvent by rotary evaporation, and purify by column chromatography to obtain a dendrimer compound.
[0028] Preferably, the preparation method of the dispersant with R=--OH is as follows:
[0029] Under a nitrogen atmosphere, perylene-3,4,9,10-tetracarboxylic anhydride, a dendritic compound, and imidazole are dissolved in N,N-dimethylacetamide, the temperature is raised to 140-150° C., and stirred for 20-24 hours; after the solution is cooled, the excess compound perylene-3,4,9,10-tetracarboxylic anhydride is filtered out, the solvent is removed by distillation under reduced pressure, the obtained solid is dissolved in dichloromethane, the excess imidazole is removed by hydrochloric acid, the organic phase is collected, dried and filtered over anhydrous magnesium sulfate, and the excess solvent is removed by a rotary evaporator to obtain a red solid.
[0030] The product 1 in step 2) of the above-mentioned method for preparing the dendrimer compound is replaced with the obtained red solid, and the operation of step 2) is repeated to obtain a dispersant with R=--OH.
[0031] More preferably, the The preparation method of the dispersant is as follows:
[0032] Under a nitrogen atmosphere, phosphorus pentoxide and dichloromethane are mechanically stirred to form a slurry, which is placed at 0-5°C and cooled for 15 minutes. Under stirring, the above-obtained R=--OH dispersant is dissolved in a dichloromethane solvent and slowly added to the slurry within 2 hours. Stirring is continued at 0-5°C for 1-2 hours, and then stirred at room temperature for 2-3 hours. The added 2,6-di-tert-butyl-p-cresol is refluxed and stirred at 40-45°C for 40-45 minutes. After cooling to room temperature, the solvent is removed by rotary evaporation to obtain of dispersant.
[0033] Preferably, the method for preparing the PCB circuit board comprises the following steps:
[0034] S1. The resin, dispersant and solvent are fully stirred in proportion to obtain a mixed solution, the carbon material and the wear-resistant additive are added to a planetary ball mill, zirconium oxide grinding beads and the mixed solution are added, and after grinding for 2 to 3 hours, the mixture is filtered through a 100-mesh sieve to obtain a carbon film ink;
[0035] S2. Take a treated substrate and put it into the printer, and print the stirred carbon film ink evenly on the substrate with an ink roller, pre-dry it in an oven at 100-120°C for 10 minutes, and continue to cure it in an oven at 165-180°C for 1-1.5 hours, and then print the conductive circuit and solder the first spring brush to obtain the main PCB circuit board;
[0036] S3. Assemble and connect the circular substrate, the second spring brush and the copper foil with the main PCB circuit board to obtain the PCB circuit board.
[0037] Preferably, the PCB carbon film actuator for automobile air conditioning is prepared by the following process:
[0038] Hot riveting of brushes → oil spraying of housing → pressing of worm → PCB welding → motor welding → PCB assembly installation → gear assembly → oil spraying of gears → pressing of housing → automatic angle detection → noise detection → appearance detection → packaging and warehousing.
[0039] Beneficial Effects
[0040] The present invention has the following beneficial effects:
[0041] 1. The present invention improves the carbon film ink formula, and the prepared carbon film has good wear resistance and excellent linearity requirements, which is used in PCB carbon film actuators to improve the service life and control accuracy of air conditioners.
[0042] 2. The present invention modifies 3,4,9,10-tetracarboxylic anhydride to obtain a double-end dendronized perylene diimide derivative, and uses this structure as a dispersant for carbon black and graphite. The perylene in the structure has a large π conjugated structure, and is adsorbed on the surface of carbon black graphite through π-π interaction with carbon black and graphite structures, and is dispersed through the steric hindrance of the dendron structure at both ends, thereby improving the accuracy of the uniformity of carbon film resistance; at the same time, during curing, the polar groups on the surface of the dendron can interact with the curing molecules through hydrogen bonds or similar miscibility to improve the interaction between carbon black, graphite and the curing agent, thereby improving the peeling force between the carbon film and the substrate; at the same time, the perylene group has good stability, and adding it thereto can improve the thermal stability of the carbon film.
[0043] 3. Improve the wear resistance of carbon film by adding nano-silicon dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a schematic diagram of the main PCB circuit board of the present invention.
[0045] 100 is a first elastic brush; 200 is an arc carbon film; 300 is a substrate; 400 is a conductor;
[0046] Figure 2 , Figure 3 This is the synthetic route of the dispersant of the present invention;
[0047] Figure 4 This is the H NMR spectrum of dispersant 1 of the present invention.
[0048] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0050] The raw materials and equipment used in the embodiments and comparative examples are described as follows:
[0051] Substrate: FR-4 epoxy board, purchased from Yirun New Materials;
[0052] Carbon black: purchased from Cabot Chemicals;
[0053] Graphite: flake graphite, purchased from Sinopharm Chemical Reagents;
[0054] Bisphenol A epoxy resin: product number QF6169, purchased from Hubei Qifei Pharmaceutical;
[0055] Methylhexahydrophthalic anhydride: 4-Methylhexahydrophthalic anhydride, product number H-00968, purchased from Tianjin Xiensi Biochemical Technology;
[0056] 3,4-Epoxycyclohexylcarboxylic acid-3,4-epoxycyclohexyl methyl ester: product number E-32170, purchased from Tianjin Xiensi Biochemical Technology;
[0057] Solvent: Propylene glycol methyl ether acetate, product number P-91715, purchased from Tianjin Xiensi Biochemical Technology;
[0058] Wear-resistant additives: nano-silicon dioxide, 500 nm, KH570 modified, purchased from Zhejiang Manli Nanotechnology;
[0059] Perylene-3,4,9,10-tetracarboxylic anhydride: product number P-20000, purchased from Tianjin Xiensi Biochemical Technology;
[0060] Tert-butyl N-(2,3-dihydroxypropyl)carbamate: product number A021878, purchased from Anaiji Chemical;
[0061] 3-Brompropylene: product number W320488, purchased from Anaiji Chemical;
[0062] Hydrogen peroxide: purchased from Sinopharm Chemical Reagent Co., Ltd.
[0063] Acetic acid: product number B020052, purchased from Anaiji Chemical;
[0064] Phosphorus pentoxide: product number P116345, purchased from Shanghai Aladdin Biochemical Technology;
[0065] 2,6-di-tert-butyl-p-cresol: product number D050745, purchased from Anaiji Chemical;
[0066] Imidazole: Product No. I-10010, purchased from Tianjin Xiensi Biochemical Technology;
[0067] Tetrabutylammonium bromide: product number T818796, purchased from Shanghai MacLean Biochemical Technology;
[0068] Dendritic compound: Homemade, preparation method is as follows:
[0069] 1) Under a nitrogen atmosphere, at a temperature of 0 to 5° C., 3 eq of tert-butyl N-(2,3-dihydroxypropyl)carbamate, 1.5 eq of tetrabutylammonium bromide (TBAB) and 30 eq of dichloromethane solvent were added to a three-necked flask, and then 3.2 eq of 3-bromopropylene and 15 eq of a 9 to 10 mol / L sodium hydroxide aqueous solution were added. The temperature was raised to 25 to 30° C., and the mixture was stirred for 12 h. Then, 50 eq of water was added for dilution, and the mixture was extracted three times with 100 eq of dichloromethane, dried over anhydrous magnesium sulfate, the solvent was removed by rotary evaporation, and the product 1 was purified by column chromatography;
[0070] 2) Under a nitrogen atmosphere, at a temperature of 0 to 5° C., 3.0 eq of hydrogen peroxide was slowly added dropwise to 1 eq of acetic acid, and stirred for 1 h to obtain a peroxide compound; 1 eq of the product 1 obtained in step 1) was dissolved in dichloromethane, and 1.5 eq of the peroxide compound was slowly added dropwise at a temperature of 0 to 5° C., the temperature was raised to 25° C. and stirred for 8 h, an excess of saturated sodium bicarbonate solution was added, and stirring was continued for 6 h, and the mixture was extracted with dichloromethane three times, dried over anhydrous magnesium sulfate, the solvent was removed by rotary evaporation, and the product 2 was purified by column chromatography.
[0071] 3) The obtained product 2 is reacted in the order of step 1), step 2), and step 1) for three steps, and then the product is dissolved in a mixed solution of dichloromethane and trifluoroacetic acid at a temperature of 0 to 5° C., wherein the volume ratio of dichloromethane to trifluoroacetic acid is 1:1, and the temperature is raised to 35° C., and after stirring for 1 hour, an excess of saturated sodium bicarbonate solution is added, and the mixture is extracted with dichloromethane three times, dried over anhydrous magnesium sulfate, and the solvent is removed by rotary evaporation. The dendrimer compound is purified by column chromatography.
[0072] Dispersant 1: Homemade, preparation method is as follows:
[0073] Under nitrogen atmosphere, 2.0 eq of perylene-3,4,9,10-tetracarboxylic anhydride, 1.0 eq of dendritic compound, and 20.0 eq of imidazole were dissolved in 100 mL of N,N-dimethylacetamide, heated to 140°C, and stirred for 24 hours. After the solution was cooled, the excess compound perylene-3,4,9,10-tetracarboxylic anhydride was filtered out, and the solvent was removed by vacuum distillation. The obtained solid was dissolved in dichloromethane, and the excess imidazole was removed with 2 mol / L hydrochloric acid. The organic phase was collected, dried and filtered over anhydrous magnesium sulfate, and the excess solvent was removed by rotary evaporator to obtain a red solid.
[0074] The obtained red solid replaces the product 1 in step 2) of the above-mentioned method for preparing the dendrimer compound, and the operation of step 2) is continued to obtain the dispersant 1.
[0075] Dispersant 2
[0076] Under a nitrogen atmosphere, 0.06 eq of phosphorus pentoxide and 50 mL of dichloromethane were mechanically stirred to form a slurry, which was cooled at 0-5°C for 15 min. Under stirring, 0.36 eq of the obtained dispersant 1 was dissolved in dichloromethane solvent and slowly added to the slurry within 2 h. Stirring was continued at 0-5°C for 1 h and then at room temperature for 2 h. 50 mg of 2,6-di-tert-butyl-p-cresol was added, and the mixture was refluxed and stirred at 40-45°C for 45 min. After cooling to room temperature, the solvent was removed by rotary evaporation to obtain dispersant 2.
[0077] Examples 1 to 4 and Comparative Examples 1 to 3
[0078] A method for preparing a PCB circuit board comprises the following steps:
[0079] S1. The epoxy resin, curing agent, diluent, dispersant and solvent are fully stirred in proportion to obtain a mixed solution, the carbon material and wear-resistant additive are added to a planetary ball mill, zirconium oxide grinding beads and the mixed solution are added, and after grinding for 2 hours, the mixture is filtered through a 100-mesh sieve to obtain a carbon film ink; specifically, the formula of the carbon film ink is shown in Table 1.
[0080] S2. Take a treated substrate and put it into the printer, and evenly print the stirred carbon film ink on the substrate with an ink roller, pre-dry it in an oven at 100°C for 10 minutes, and then continue to cure it in an oven at 170°C for 1h, and then print the conductive circuit and solder the first spring brush to obtain the main PCB circuit board;
[0081] S3. Assemble and connect the circular substrate, the second spring brush and the copper foil with the main PCB circuit board to obtain the PCB circuit board.
[0082] Table 1 Carbon film ink formulations of Examples 1 to 4 and Comparative Examples 1 to 3 (parts by mass)
[0083] Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Carbon Black 15 25 22 22 22 22 22 graphite 5 10 8 8 8 8 8 Epoxy resin 8.6 10 8 8 8 8 8 Curing agent 8.6 10 8 8 8 8 8 Thinner 17.1 15 16 16 16 16 16 Solvent 5 10 8 8 8 8 8 Wear-resistant additives 1 1.5 1.2 1.2 1.2 1.2 Dispersant 1 1.5 2.5 2.1 2.1 3.6 Dispersant 2 2.1
[0084] A PCB carbon film actuator, the PCB carbon film actuator comprising a housing, a PCB circuit board, a first rotating gear, a second rotating gear, a third rotating gear, an output gear and a driving assembly; the PCB circuit board comprises a main PCB circuit board and a circular PCB circuit board; the main PCB circuit board comprises a substrate (300), a first spring brush (100), a wire (400) and a circular arc carbon film (200); the schematic diagram of the main PCB circuit board is as follows Figure 1 As shown; the circular PCB circuit board includes a circular substrate, a second spring brush and a copper foil; one end of the first spring brush is fixed to the main PCB circuit board, and one end is in contact with the copper foil, and is used to connect the circular PCB circuit board with the circular PCB circuit board; one end of the second spring brush is fixed to the edge of the circular PCB circuit, and one end is in contact with the arc carbon film, and slides on the arc carbon film through the rotation of the output gear; the arc carbon film is obtained by printing carbon film ink on the substrate and curing. The PCB circuit board is the PCB circuit board corresponding to Examples 1 to 4 and Comparative Examples 1 to 3.
[0085] The PCB carbon film actuator is manufactured by the following process:
[0086] Hot riveting of brushes → oil spraying of housing → pressing of worm → PCB welding → motor welding → PCB assembly installation → gear assembly → oil spraying of gears → pressing of housing → automatic angle detection → noise detection → appearance detection → packaging and warehousing.
[0087] The following is the test method for the performance parameters involved in the present invention:
[0088] (1) Peel strength: The carbon film is tested on the test pattern O according to the test method of 7.1 test 10a in GB / T 4677-2002;
[0089] (2) Wear resistance: The carbon film was tested using the test method in 6.9.1 of SJ / T 11171-2016, with a resistance change of 500,000 times;
[0090] (3) Linearity requirement: Rotate the potentiometer 10°, 30°, 60°, 90°, and 120° to test the potentiometer carbon film resistor. Repeat three times and take the average value. Use this angle and resistance data to perform linearity analysis.
[0091] Table 2 Performance test
[0092] <![CDATA[Peeling strength (N / mm 2 )]]> Wear resistance (%) Linearity requirement (%) Example 1 1.9 4.3 0.75 Example 2 1.8 4.1 0.62 Example 3 2.0 4.0 0.58 Example 4 2.6 3.5 0.31 Comparative Example 1 1.2 4.7 0.96 Comparative Example 2 1.6 9.5 0.82 Comparative Example 3 2.4 3.3 0.85
[0093] It can be seen from the data in Table 2 that the addition of the dispersant prepared by the present invention can improve the peel strength and linearity requirements of the carbon film, and the addition of nano-silicon dioxide can improve the wear resistance.
[0094] Among them, it can be seen from Examples 3 to 4 that the addition of dispersant 2 has better performance than dispersant 1. After the hydroxyl group is modified to a phosphate group, the dispersing ability for carbon black and graphite is stronger. From the data of Comparative Examples 1 and 2, it can be seen that not adding nano-silicon dioxide and the dispersant prepared by the present invention will lead to a decrease in performance; from the data of Comparative Example 3, it can be seen that adding too much dispersant of the present invention will lead to a decrease in performance. This is because too much dispersant itself will have a certain aggregation, resulting in a decrease in its dispersing ability. Among them, the improvement of dispersion improves the control accuracy of the controller, and the improvement of wear resistance and peel strength increases the service life of the controller.
[0095] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A PCB carbon film actuator for automobile air conditioning, characterized in that: The PCB carbon film actuator is composed of a housing, a PCB circuit board, a first rotating gear, a second rotating gear, a third rotating gear, an output gear and a driving component; the PCB circuit board includes a main PCB circuit board and a circular PCB circuit board; the main PCB circuit board includes a substrate, a first spring brush, a wire and a circular carbon film; the circular PCB circuit board includes a circular substrate, a second spring brush and a copper foil; one end of the first spring brush is fixed to the main PCB circuit board, and one end is in contact with the copper foil, and is used to connect the circular PCB circuit board with the circular PCB circuit board; one end of the second spring brush is fixed to the edge of the circular PCB circuit, and one end is in contact with the circular carbon film, and slides on the circular carbon film through the rotation of the output gear; The arc carbon film is obtained by printing carbon film ink on a substrate and curing it; the carbon film ink comprises the following components by weight: 20 to 35 parts of carbon material, 30 to 35 parts of resin, 1.5 to 2.5 parts of dispersant, 5 to 10 parts of solvent, and 1 to 1.5 parts of wear-resistant additive; the dispersant has the following molecular structure of Formula I: R in the molecular structure of Formula I is one or more of the following molecular structures: --OH, --Cl and 2. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The substrate is one or more of a paper substrate, a glass cloth substrate and a composite substrate.
3. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The carbon material is at least one of carbon black and flake graphite.
4. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The driving assembly includes a motor and a worm; the first rotating gear is composed of a helical gear and a spur gear; the second rotating gear, the third rotating gear and the output gear are composed of spur gears; the worm of the driving assembly rotates to drive the first rotating gear, the first rotating gear is toothed with the second rotating gear, the second rotating gear is toothed with the third rotating gear, and the third rotating gear is toothed with the output gear.
5. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The resin consists of epoxy resin, curing agent and diluent, and the mass ratio of the epoxy resin, curing agent and diluent is 1:1:1.
5.
6. A PCB carbon film actuator for automobile air conditioner as claimed in claim 5, characterized in that: The epoxy resin is bisphenol A epoxy resin; the curing agent is at least one of methyl hexahydrophthalic anhydride and hexahydrophthalic anhydride; and the diluent is at least one of 3,4-epoxycyclohexylcarboxylic acid-3,4-epoxycyclohexyl methyl ester and glycidyl alkyl ether.
7. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The solvent is at least one of ethylene glycol butyl ether and propylene glycol methyl ether acetate; and the wear-resistant additive is nano silicon dioxide.
8. A PCB carbon film actuator for automobile air conditioner as claimed in claim 1, characterized in that: The PCB circuit board is made by the following method: S1. The resin, dispersant and solvent are fully stirred in proportion to obtain a mixed solution, the carbon material and the wear-resistant additive are added to a planetary ball mill, zirconium oxide grinding beads and the mixed solution are added, and after grinding for 2 to 3 hours, the mixture is filtered through a 100-mesh sieve to obtain a carbon film ink; S2. Take a treated substrate and put it into the printer, and evenly print the stirred carbon film ink on the substrate with an ink roller, pre-dry it in an oven at 100 to 120°C for 10 minutes, and continue to cure it in an oven at 165 to 180°C for 1 to 1.5 hours, and then print the conductive circuit and solder the first spring brush to obtain the main PCB circuit board; S3. Assemble and connect the circular substrate, the second spring brush and the copper foil with the main PCB circuit board to obtain the PCB circuit board.
9. A PCB carbon film actuator for automobile air conditioner as claimed in claim 8, characterized in that: The PCB carbon film actuator is manufactured by the following process: Hot riveting of brushes → oil spraying of housing → pressing of worm → PCB welding → motor welding → PCB assembly installation → gear assembly → oil spraying of gears → pressing of housing → automatic angle detection → noise detection → appearance detection → packaging and warehousing.
Citation Information
Patent Citations
Water-soluble dendrimer-like perylene monoimide compound fluorescent probe as well as preparation method and application thereof
CN106188102A
Preparation method of graphene coating aluminum foil
CN110707328A